Pesticide screening and health risk assessment of residential dust in a rural region of the North China Plain. (September 2022) - Mu, Hongyu; Zhang, Jingcheng; Yang, Xiaomei; Wang, Kai; Xu, Wen; Zhang, Hongyan; Liu, Xuejun; Ritsema, Coen J.; Geissen, Violette
Abstract: Pesticides that have accumulated in arable soil could be easily transported by wind erosion, thereby potentially threating air quality and human health in surrounding areas. The risks this poses to farmers exposed to pesticide-associated dust is still unknown, especially in rural areas of China. In this study, we screened pesticide residues in dust (indoor and outdoor) collected from the homes and yards of pesticide sprayers (21 participants) and farm workers (14 participants) living in Quzhou County located in the North China Plain to assess health risks by exposed to pesticide-contaminated dust. The results showed that multiple pesticide residues were detected in the dust samples and more than 90% of the samples contained over 10 pesticide residues. The maximum detected number of residues was 23, out of the 25 pesticides currently used in the farming area. There was a wide range of pesticide concentrations with the geometric mean values measuring between 0.03 and 0.86 mg kg −1 . More residues and higher concentrations of pesticides were detected in indoor dust compared to outdoor dust. Over the monitoring period, the pesticide application has not caused significant pesticide accumulation in dust. The measured concentrations of carbendazim, dimethomorph, dimethomorph and pendimethalin paired indoor-outdoor dust samples were significantly correlated (p < 0.05). The health risks were assessed using the hazard index (HI) and highest HI was found for children under indoor exposure (HI = 0.82). In addition, based on the survey and statistics, pesticide preparation in the home was significantly correlated with the pesticide indoor exposure level. Therefore, farmers should take measures, such as preparing pesticides outside of the house or in the open fields with protection, in order to avoid the exposure risk of pesticides associated with dust. Graphical abstract: Image 1 Highlights: Dust in pesticide sprayers' residences exhibits higher pesticide concentrations. Higher accumulation levels of pesticides were found in indoor dust. Health risks of pesticides in indoor dust should be aware especially for children. Preparing pesticides inside homes contributes to indoor pesticide exposure risks.